People's Republic of China : Financial Sector Assessment Program- Detailed Assessment of Observance of the Iosco Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents an assessment of the level of observance of the IOSCO Objectives and Principles of Securities Regulation in China. The regulatory framework and supervisory program for the securities markets is largely compliant with the IOSCO Principles. Since 2010, the authorities have implemented several initiatives aimed at protecting China's very large retail investor population. On the China Securities Regulatory Commission (CSRC) side, this includes strengthening the suitability requirements for intermediaries, investors' ability to exercise their rights, and its investor education program. The CSRC has also expanded authorized activities for some categories of securities intermediaries with the objective of developing an investment banking culture to help capital markets serve the real economy better.